Knowledge and feelings of quilombola women about cervical cancer - Souza , Thais Gonçalves de; Pereira Alves, Beatriz; Lira da Silva, Anna Beatryz; Alves Barbalho, Isabela Lunara; de Abreu Temoteo, Rayrla Cristina; Costa Fernandes, Marcelo (Revista de Enfermagem da UFPI, 2022)
Objective: To identify the knowledge and feelings of quilombola women about cervical cancer. Methods: A descriptive study with a qualitative approach, mediated by the action-research methodology, in which 12 quilombola women participated. Data collection was carried out through semi-structured interviews, analyzed using the Collective Subject Discourse technique. Results: It was evidenced that women have a perception of the severity of the disease, although they demonstrate some difficulty in defining its basic characteristics; demonstrate some knowledge when talking about some of the risk factors, that already have scientific evidence of cervical cancer, however, superficiality was noticed in their speeches. In addition, there was a predominance of negative feelings linked to a possible diagnosis, as well as the consequences of the treatment, evidencing a certain vulnerability to coping with the disease. Conclusion: Gaps were observed in the knowledge of quilombola women about cervical cancer, as well as the specificities of their preventive methods and their consequences in the quality of life of quilombola women, such as fear, shame and the consequence of self-neglect in the way these women deal with the disease and their preventive methods.